1993
DOI: 10.1084/jem.178.2.675
|View full text |Cite
|
Sign up to set email alerts
|

Anhydroretinol: a naturally occurring inhibitor of lymphocyte physiology.

Abstract: Stlmmsl'y Vitamin A (retinol) is an essential cofactor for growth of B lymphocytes in culture and for activation ofT lymphocytes by antigen receptor-mediated signals. 14-hydroxy-4,14-retro-retinol (14-HKR) a metabolite of retinol, has been implicated as the intraceUular mediator of this effect. Anhydroretinol (AR) is a retinol derivative with retro structure produced in activated human B lymphocytes and the insect cell lines SF 21 and Schneider $2. AK reversibly inhibits retinol-and 14-HKKdependent effects and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 26 publications
(22 reference statements)
4
44
0
Order By: Relevance
“…These observations are in line with recent findings indicating that retinoids are important cofactors in murine T-cell activation and proliferation (7). Different vitamin A metabolites seemingly are physiological modulators, which control the proliferation and differentiation of lymphoid and myeloid cells (2,6). Thus, RA-induced HOXB gene induction may reflect a physiologic mechanism underlying T-cell activation.…”
supporting
confidence: 79%
“…These observations are in line with recent findings indicating that retinoids are important cofactors in murine T-cell activation and proliferation (7). Different vitamin A metabolites seemingly are physiological modulators, which control the proliferation and differentiation of lymphoid and myeloid cells (2,6). Thus, RA-induced HOXB gene induction may reflect a physiologic mechanism underlying T-cell activation.…”
supporting
confidence: 79%
“…They demonstrated that the retinol metabolite 14-hydroxy-4,14-retro-retinol (14-HRR) is responsible for the effects, and that anhydro-retinol reversed the effects of 14-HRR (Buck et al, 1991(Buck et al, , 1993. Similar effects have been observed in fibroblasts and promyelocytes: 14-HRR is a growth factor, whereas anhydro-retinol is an antagonist of the growth-promoting effect of 14-HRR.…”
Section: Mechanism Of Action Of Retro-retinoids Retinol and Other Rmentioning
confidence: 54%
“…As previously reported, lymphocytes (normal T cells, transformed lymphoblastoid B cells, and T leukemia cells) undergo rapid PCD during nutritional vitamin A deprivation, when internal stores of retinyl-ester become depleted (6,16,47). Throughout our work AR is used as a tool to induce an acute state of vitamin A deficiency.…”
Section: Discussionmentioning
confidence: 87%